Functional data analysis of joint coordination during the pull of the power clean - Nagatani, T.; Vial, S.; Kendall, K. L.; Comfort, P.; Haff, G. G. (Sports Biomechanics, 2026)
The purpose of this study was to use a bivariate functional principal component analysis (bfPCA) to quantify hip-knee joint movement patterns and assess their relationship with power clean performance. Thirty strength-power athletes completed a one repetition maximum (1RM) power clean test where hip and knee joint angle data from the heaviest successful lift were recorded and analysed using bfPCA. Three principal components were extracted, primarily reflecting variability in hip joint angle throughout the pull (pattern 1), knee joint angle at the starting position (pattern 2), hip-knee joint motion from the middle of the first pull through to the end of the second pull (pattern 3). Correlation analyses revealed no significant or meaningful correlations between power clean performance and patterns 1 or 2 (r = -0.10 and 0.04, p = 0.60 and 0.85, respectively), suggesting that inter-individual differences in starting position may not negatively impact power clean performance. However, pattern 3 was weakly but significantly correlated with power clean performance (r = 0.39, p = 0.03), with higher-performing lifters displaying movement patterns characterised by a more upright torso at the power position and a more controlled, prolonged first pull. These findings suggest that coaches focus on these aspects of the movement to potentially maximise power clean performance.